Venezuelan migration in northern Chile: the case of unaccompanied migrant children: Venezuelan migration in northern Chile: the case of unaccompanied migrant children (Simbiótica. Revista Eletrônica, 2023)
During the last decade, the Chilean State has generated various administrative measures to order and regulate migratory flows. In this scenario, it is identified that, because of the border closure due to the pandemic, and the implementation of restrictive migration policies adopted by the Chilean Government since 2018 the irregular entry and administrative sanctions of thousands of foreign citizens, particularly of Venezuelan origin. One of the effects detected in the restrictive management of these flows was the entry of unaccompanied foreign children and adolescents through unauthorized passes, located in the extreme north of Chile. However, the objective of this study was to learn, from an exploratory perspective, about the response generated by the Chilean State in dealing with unaccompanied migrant children and their protection. To this end, we interviewed people involved in migrant children's issues and institutional informants working in the field. We conclude that, despite the timid efforts of the judiciary to address unaccompanied migrant children, the Chilean State has not been able to safeguard the protection of unaccompanied children and adolescents in contexts of forced mobility.